Spontaneous Rupture of the Bile Duct Associated with Pancreatitis. A Rare Presentation - Goenka, Mahesh K; Acharyya, Bhaswati C; Sethy, Pradipta K; Goenka, Usha (JOP. Journal of the Pancreas, 2011)
Context Spontaneous rupture of the bile duct, although rare, has been described as a known surgical cause of jaundice in infancy after biliary atresia. Case report This article describes a four-year-old girl who presented with severe abdominal pain and features suggestive of acute pancreatitis, who developed gradual distension of the abdomen, and was found to have a ruptured bile duct, producing biliary peritonitis. She was managed with laparoscopic drainage of the peritoneal cavity. However, in view of the persistent biliary drainage, an ERCP was performed followed by stent placement for a bile duct leak. She was subsequently diagnosed as having a choledochal cyst. Conclusion A high index of suspicion, appropriate investigation, such as MRCP, combined with early drainage can help in reaching an early diagnosis, and reduced morbidity and mortality in this rare disorder. Image: Initial ERCP showing a leaking bile duct, biliary sphincterotomy and stenting.